P08.21 Sex and pelvic inflammatory disease: what's the relationship? case-control study. (13th September 2015) - Low, N; Hegazi, A; Chan, S-Y; Hay, P; Herzog, SA
Abstract : Background: Pelvic inflammatory disease (PID) results from infection ascending to the upper female genital tract. The timing of progression of untreated infections is poorly understood and difficult to study prospectively. We investigated temporal relationships between recent sexual partnerships and PID caused by the sexually transmitted infections (STI) Chlamydia trachomatis or Neisseria gonorrhoeae . Methods: We did a case-control study, using case records. Cases were women with clinically diagnosed PID and a positive C. trachomatis or N. gonorrhoeae test result. Control groups were women who presented on the same day with: control1) clinical PID and negative test results; control 2 ) no clinical PID and negative test results; control3) uncomplicated C. trachomatis or control4) uncomplicated N. gonorrhoeae infection. We used survival methods for statistical analysis. Results: We analysed data from 356 women: 72 cases, 83 control1, 75 control 2, 68 control3 and 58 control4. Cases and women in control3 and control4 were younger than women in control1 or control 2 (p < 0.001), intrauterine device use and dates of last menstruation before attendance were similar in all groups. Women with chlamydial or gonococcal PID (cases) had more recently changed sexual partners (median 154 days, IQR 61–736) than those with clinical PID but no infection (control1, median 367 days, IQR 94–1419, p = 0.082). The time from the start of the most recent sexual partnership to symptom onset was shorter in cases (median 121 days, IQR 47–695) than control1 (median 366 days, IQR 104–1552, crude hazard ratio, HR 0.65, 95% CI 0.46–0.92). After adjusting for age, this association was weakened (adjusted HR 0.81, 95% CI 0.56–1.17). Conclusion: Differences in the course of STI- and non-STI associated PID were mainly due to age. Further studies to elucidate the course of acute STI and ascending infection will help to understand the impact of screening and treatment interventions on PID prevention. Disclosure of interest: No funding was received for this study.